Three little movements in modern “mission”: Part I – Incarnation, disclosure, witness, and reconciliation in the SCA cross-cultural missions programme: 1979–1985 - Goddard, Allen James (Stellenbosch Theological Journal, 2023)
René Padilla’s invitation to evangelicals worldwide, to take up integral mission, in the 1960s, 70s and 80s, and the South African invitation to embrace “transforming mission” in cross-cultural ministries closely associated with the work of David Bosch and Klippies Kritzinger, were clarion calls to the global church, to turn back to the source of “mission,” which is Jesus, forming in his followers a new eschatological identity that empowers us to be witnesses who embody Christ’s good news of reconciliation. Among all who took up this invitation to realize an incarnational and contextual gospel, were evangelists in South Africa’s Students’ Christian Association, who created the SCA Cross-Cultural Missions’ Programme, or SCAMP, in 1979. This article is the first of three, which draw on a repository of memories catalogued through the discipline of oral history research; the writer’s own experience of training and teaching in the SCAMP programme; long-time friendships with many SCAMP people of the 1980s; a wide range of gathered archival primary sources; and published missiology and historiography, to construct a preliminary history of SCAMP during the 1980s at the zenith of the apartheid era. The narrative will be periodized into three distinct historical sequences, each of which may offer learnings for the contemporary church in its current understandings of “mission,” for a more incarnational, prophetic, and deeply empathic embodiment of Christian witness.